Ethics and Robotics. A First Approach - De Asís Roig, Rafael (The Age of Human Rights Journal, 2014)
Clearly, technical and scientific progress and moral progress do not necessarily go hand in hand. Therefore, this article encourages reflection on the new ethical challenges posed by such developments and, in particular, by robotics, a field that has developed greatly in recent decades and that has led to possibilities unimaginable until recently. Thus, the author examines here the so-called roboethics, its content, the specific fields it addresses –such as social relations and moral agency of robots–, as well as the different approaches and views on these issues.